2021
DOI: 10.2337/db21-0129
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for Different Adiposity Phenotypes and Their Opposing Influences on Ectopic Fat and Risk of Cardiometabolic Disease

Abstract: To understand the causal role of adiposity and ectopic fat in type 2 diabetes and cardiometabolic diseases, we aimed to identify two clusters of adiposity genetic variants: one with “adverse” metabolic effects (UFA) and the other with, paradoxically, “favorable” metabolic effects (FA). We performed a multivariate genome-wide association study using body fat percentage and metabolic biomarkers from UK Biobank and identified 38 UFA and 36 FA variants. Adiposity-increasing alleles were associated with an adverse … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 63 publications
3
62
0
Order By: Relevance
“…We used 696 variants from a GWAS in the UK Biobank ( Martin et al, 2021 ). We used bio-impedance measures of body fat % taken by the Tanita BC-418MA body composition analyser in 442,278 individuals of European ancestry.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used 696 variants from a GWAS in the UK Biobank ( Martin et al, 2021 ). We used bio-impedance measures of body fat % taken by the Tanita BC-418MA body composition analyser in 442,278 individuals of European ancestry.…”
Section: Methodsmentioning
confidence: 99%
“…We also identified 38 unfavourable adiposity (UFA) alleles which are associated with higher fat in subcutaneous and visceral adipose tissue, and higher ectopic liver and pancreatic fat ( Ji et al, 2019 ; Martin et al, 2021 ), resembling monogenic obesity ( Supplementary file 1a ). We performed MR studies and showed that FA and UFA have opposite causal effects on six metabolic conditions ( Martin et al, 2021 ). While both FA and UFA were associated with higher adiposity, FA was causally associated with lower risk of type 2 diabetes, heart disease, hypertension, stroke, polycystic ovary syndrome, and non-alcoholic fatty liver disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 A second category of studies has aimed to gain further resolution into anthropometric loci by combining summary statistics of metabolic and anthropometric traits, generating clusters of metabolically favorable and unfavorable loci. [18][19][20][21][22] These studies have succeeded in establishing a common variant basis for metabolically distinct fat depots, with seminal work demonstrating that an insulin resistance polygenic score is associated with lower hip circumference in the general population, and that individuals with familial partial lipodystrophy type 1 (FPLD1) have a higher burden of this polygenic score. 19 Along with their reliance on anthropometric proxies of fat distribution, these studies are limited by their inclusion requirement of nominal significance across multiple metabolic traits which is likely leading to only a fraction of the genetic architecture of fat distribution being described.…”
Section: Introductionmentioning
confidence: 99%